Immunochemotherapy and Maintenance With Obinutuzumab or Rituximab in Patients With Previously Untreated Marginal Zone Lymphoma in the Randomized GALLIUM Trial. Issue 3 (24th March 2022) - Herold, Michael; Hoster, Eva; Janssens, Ann; McCarthy, Helen; Tedeschi, Alessandra; Pocock, Chris; Rosta, Andras; Trněný, Marek; Nielsen, Tina G.; Knapp, Andrea; Hiddemann, Wolfgang; Marcus, Robert
Abstract : The aim of this study was to explore the efficacy and safety of obinutuzumab (G)- versus rituximab (R)-chemotherapy in a subgroup of patients with previously untreated marginal zone lymphoma (MZL) in the phase III GALLIUM trial (NCT01332968). Patients had stage III/IV (or stage II with bulky disease), splenic, nodal, or extranodal MZL requiring treatment. Patients were randomized 1:1 to receive G- or R-chemotherapy (cyclophosphamide, doxorubicin, vincristine, and prednisone; cyclophosphamide, vincristine, and prednisone; or bendamustine, allocated at patient level). Patients with complete/partial response at the end of induction (EOI) received G/R maintenance. Investigator-assessed progression-free survival (PFS), other time-to-event endpoints, response, and safety were assessed. Overall, 195 patients with MZL were included in this analysis: G-chemotherapy (n = 99), R-chemotherapy (n = 96). Median observation time: 59.3 months. No meaningful difference was observed between arms for PFS (4-y PFS rates: G-chemotherapy, 72.6%; R-chemotherapy, 64.1%), other time-to-event endpoints, or EOI response rates (by computed tomography [CT; G-chemotherapy, 81.8%; R-chemotherapy, 81.3%] and positron emission tomography CT [G-chemotherapy, 79.2%; R-chemotherapy, 87.5%]). All patients experienced ≥1 adverse event (AE). G-chemotherapy was associated with a higher incidence of grade 3–5 (86.1% versus 77.4%), grade 5 (14.9% versus 9.7%), and serious (66.3% versus 51.6%) AEs versus R-chemotherapy. Both arms had a higher incidence of grade 3–5 and serious AEs than patients with follicular lymphoma (GALLIUM), with G-chemotherapy being less tolerable than R-chemotherapy. Based on the observed tolerability of G-chemotherapy versus R-chemotherapy, and the comparable efficacy of G-chemotherapy and R-chemotherapy in this analysis, G-chemotherapy cannot be recommended as first-line treatment for MZL.